Safety and Efficacy of Multiple Drug Resistant Tuberculosis Treatment in Patients with Different HIV Statuses - S. Yu. Degtyareva; V. N. Zimina; А. V. Pokrovskaya; G. V. Volchenkov (Туберкулез и болезни лёгких)
The objective: to analyze and compare frequency and variety of adverse events (AEs) and their impact on outcomes of tuberculosis therapy when treating patients with multiple drug resistant tuberculosis (MDR TB) and different HIV statuses.Subjects and Methods: retrospective observational case-control study of patients registered for treatment with the 4th regimen of chemotherapy for tuberculosis in the city of Vladimir and Vladimir Region in 2014-2016.Results. The proportion of patients who reported any AE during the MDR TB treatment was similar among HIV positive and HIV negative patients and made 85.5%. In patients with concurrent HIV infection and MDR TB, hematopoietic AEs such as anemia, thrombocytopenia were more frequent, while neutropenia was significantly more frequent when comparing groups by the cumulative event probability method. Elevated eosinophil level during treatment was more typical of MDR TB patients. Treatment outcomes in the group of patients with HIV and MDR TB were statistically significantly worse due to the higher frequency of fatal outcomes. At the same time, there was no correlation of AE with unfavorable treatment outcomes. The early initiation of combination therapy with thorough monitoring of hematologic parameters in patients with HIV and MDR TB was safe and effective.